Pengaruh Gaya Kepemimpinan, Kompensasi dan Sanksi Terhadap Kinerja Pegawai Perum Bulog Sub Divisi Regional II Parepare - Arifuddin Arifuddin; Aryati Arfah; Muhammad Arif (AhInstitute of Research and Community Service (LP2M) Institute of Social Sciences and Business Andi Sapada, 2023)
This study aims to determine partially the influence of leadership style, compensation, and sanctions on the performance of employees of the Perum Bulog Sub Division Regional II Parepare. To determine simultaneously the influence of leadership style, compensation, and sanctions on the performance of employees of Perum Bulog Regional Division II Parepare. Data collection techniques that researchers use in this research are observation, interviews, questionnaires, and documentation. The population in this study was the researchers, namely all employees of Perum Bulog Regional Sub Division II Parepare, totaling 37 people. In order for this research to be precise and professional, in this research a saturated sample technique was used, meaning that all employees of Perum Bulog Regional Sub Division II Parepare with a total of 37 people. The results of this study indicate that leadership style has no significant effect partially on the performance of the employees of Perum Bulog Regional Sub Division II Parepare. Compensation has a partially significant effect on the performance of employees of Perum Bulog Regional Sub Division II Parepare. Sanctions do not have a significant effect partially on the performance of employees of Perum Bulog Regional Sub Division II Parepare. Leadership style, compensation, and sanctions have a significant effect simultaneously. on the performance of employees of Perum Bulog Regional Sub Division II Parepare. The R square or R squared value obtained is 0.251 meaning that leadership style, compensation, and sanctions on employee performance have an effect of 21.1% while the remaining 74.9% is influenced by variables not examined such as work motivation, work environment, training work, and so on.